Большие данные. Аналитические базы данных и хранилища: Greenplum - Урсатьев, А.А. (Управляющие системы и машины, 2019)
Статья представляет собой продолжение исследований Больших Данных и инструментария, трансформируемого в новое поколение технологий и архитектур платформ баз данных и хранилищ для интеллектуального вывода. Рассмотрен ряд прогрессивных разработок известных в мире ИТ-компаний, в частности Greenplum DB. Мета. Розглянути та оцінити ефективність застосування інфраструктурних рішень нових розробок в дослідженнях Великих Даних для виявлення нових знань, неявних зв'язків і поглибленого розуміння, проникнення в суть явищ і процесів. Методи. Інформаційно-аналітичні методи і технології обробки даних, методи оцінки та прогнозування даних, з урахуванням розвитку найважливіших галузей інформатики та інформаційних технологій. Результати. Greenplum, так само як Netezza і Teradata, створив свій комплекс Data Computing Appliance, пізніше – аналітичну БД Pivotal Greenplum Database корпоративного класу з потужною і швидкою аналітикою для великих обсягів даних під торговою маркою Pivotal. Purpose. The purpose is to consider and evaluate the application effectiveness of the infrastructure solutions for new developments in the Big Data study, to identify new knowledge, the implicit connections and indepth understanding, insight into phenomena and processes. Methods. The informational and analytical methods and technologies for data processing, the methods for data assessment and forecasting, taking into account the development of the most important areas of the informatics and information technology. Results. Greenplum, as well as Netezza and Teradata, created its Data Computing Appliance (DCA) complex, and later, an analytical Pivotal database Greenplum Database of corporate class with powerful and fast analytics for large data volumes under the Pivotal trademark.